Legal Interpretation of Terms, Phrases, and Clauses in the Notarial Deeds - Suryadi, Suryadi; Rahayu, Triwati (Jurnal Hukum Novelty, 2023)
Introduction to The Problem: A notarial deed is an authentic deed containing various legal relationships or events with specific characteristics drafted by or attested by a notary. Its peculiarities vary based on the form, structure, and legal language that are not easily understood by other legal practitioners or the public. To avoid a dispute between the parties, an interpretation of the terms of the legal language used in the deed is required. Based on the literature review, previous studies have yet to discuss the legal interpretation of the deeds made by a notary.Purpose/Objective Study: The research aims to identify and describe the legal interpretation of the terms, phrases, and clauses used in notarial deeds.Design/Methodology/Approach: This research is normative-empiric research. Data consists of primary and secondary data. There are 20 deeds of Islamic financing contracts and ten various deeds such as co-operation agreements, repurchase agreements, bank loans, and so on. The deeds were drafted and/or attested by Sari Darmawati, S.E., S.H. notary in Semarang. Findings: The legal interpretation of notarial deeds is pivotal for ensuring the enforceability of agreements, drawing on legal sources like laws and judicial decisions. Standardized terms form a foundational framework, although their unique meanings may be complex for the public. Gender-based designations and clauses regarding breach of contract and force majeure define legal consequences. In Islamic finance, specific definitions are introduced. Emphasizing jurisdiction and legal principles in agreements, parties' intention prevails in case of ambiguity. Progressive law advocates for a functional interpretation, considering social realities. Interpreting notarial deeds demands a nuanced understanding of language and party intentions, requiring adherence to legal principles amid evolving societal dynamics.Paper Type: Research Article